До питання про тенденції розвитку сучасної авторської лексикографії - Козирєва, З. (Лексикографічний бюлетень, 2018)
In articlethe achievements of modern lexicography in the creation of standard dictionaries are highlighted. Dictionaries of different types and genres are considered. The vocabulary of the language of the creative personality is considered as an opportunity through the means and means of verbalization of individual world modeling to know the ideology of the artist – the phenomenon of his linguistic personality. It is emphasized on the necessity of systematic study of the lexical composition of modern Ukrainian language, which provides a combination of the main branches of academic lexicography. The sources of the vocabulary of the language of the creative personality are highlighted, the purpose of the lexicographic study of the lexical – phraseological system of the Ukrainian language is outlined taking into account the latest theoretical and practical achievements of the national lexicology, phraseology and lexicography. The main steps in the development of Ukrainian academic lexicography are outlined,the source base for the vocabulary of the creative linguistic personality is characterizedas a basis for creating an active vocabulary dictionary.